The maternal image in a child raised by a childless relative: a case study using the Rorschach test - boualagua, fatima (Journal of Social Sciences and Humanities, 2016)
This article addresses the issue of a child raised by a childless relative and the extent to which the dual bond between the biological mother and the foster mother influences the child. It explores the dialectical question of whether this child develops like any other child or, conversely, differs from other children due to a problematic sense of belonging. We focus on this topic in order to examine the nature of the maternal image in the child under care, and whether this dual affiliation places the child in difficulty during the pre-genital and genital stages of development, especially during the latency period in which signs of autonomy and individuation become more apparent. To answer these questions, we present a case study of a 12-year-old girl raised by her maternal aunt, who is childless, analyzed through the Rorschach Inkblot Test.